Bibliometric study of articles published in a Brazilian journal of pediatric dentistry - Vanessa Ceolin Poletto; Italo Medeiros Faraco Junior (Sociedade Brasileira de Pesquisa Odontológica, 2010)
This cross-sectional study aimed at evaluating the abstracts of all articles published in the "Jornal Brasileiro de Odontopediatria e Odontologia do Bebê" in order to collect data on the study design used, the most researched topics and the Brazilian states with the highest scientific production. Copies were made of the abstracts of each article, totaling 572 abstracts. Data categorization was done by two trained and independent reviewers. The results showed that the most used study design were case report (33%) and cross-sectional study (30%). On the other hand, there were only 2.5% of randomized clinical trials and no systematic review or meta-analysis. The most researched topics were cariology (15%) and restorative dentistry / dental materials (10%). The state with the greatest number of publications was São Paulo (40%), followed by Rio de Janeiro (17%). It was concluded that the majority of the articles published referred to studies with a low potential to establish scientific evidence, indicating a need for conducting research based on better quality methodology. Moreover, it was found that the assessed literature reflected the trends observed in the clinical practice of Pediatric Dentistry in Brazil.